OPTIMALISASI SISTEM ANTRIAN PADA SPBU 64.708.13 MENGGUNAKAN STRKTUR MCMS (Multi channel-Single Phase) - Ice Trianiza; Abdurahim Sidiq; Idzani Muttaqin; Nanda Fitriyani; Rizky Yanuar Akhmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
This study aims to analyze and optimize the queuing system at Fuel Station 64.708.13 in Panyipatan District, Tanah Laut Regency, using a multi-channel single-phase (M/M/S) structure to improve overall service efficiency. The study uses the First Come, First Served (FCFS) system, where customers are served in the order of arrival. The data used in this study included customer arrival times and service times, which were collected over seven days from December 16 to December 22, 2024, between 08:00 and 10:00 WITA. This data was then processed through simulations using the POM-QM for Windows software to evaluate the impact of adding service facilities on efficiency levels. The analysis results indicated that implementing three fuel dispensing facilities could reduce the service time gap by 40 seconds from the standard time that had been determined. With this three-facility configuration, the average number of customers in the system (Ls) was 2–3 customers, the number of customers in the queue (Lq) was 1 customer, the customer waiting time in the system (Ws) ranged from 0.72 to 0.79 minutes, and the customer waiting time in the queue (Wq) was between 0.09 and 0.16 minutes. These numbers indicated an improvement in efficiency compared to the standard service waiting time (Wq) of 0.665 minutes.